Sistem Pakar Diagnosa Kerusakan Motor Suzuki Smash Titan 115 Cc Menggunakan Metode Forward Chaining - Andi Seppewali; Warseno Hari Mulyo; Riswan Riswan (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Expert system is a computer-based system that uses knowledge, facts, and reasoning techniques that adapts the methods of an expert in a particular field to solve complex problems using a computer as an aid and a certain programming language. This expert system is built to assist Suzuki motorcycle users and technicians in resolving problems, especially with the Smash Titan 115 cc motorcycle. Problems with the Smash Titan 115 cc motorcycle require expert knowledge to find a solution. The expert system is built using the Forward Chaining method, where the system makes forward-based reasoning based on existing symptoms, then diagnoses the damage of each symptom of a problem and the system will draw conclusions from these symptoms. After this expert system is designed and implemented using the CodeIgniter framework and using the MySQL database, the process of searching for problems can be done quickly and accurately. In using the software that is built, the menus are designed very simply so that users can easily use it. The knowledge representation technique used in this expert system is production rules with the Best-First Search technique. Expert System, Forward Chaining, Expert Knowledge, Best first search